2019
DOI: 10.1213/ane.0000000000002570
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Basis for Regional Anesthesia in Ambulatory Arthroscopic Knee Surgery and Anterior Cruciate Ligament Reconstruction: Part II: Adductor Canal Nerve Block—A Systematic Review and Meta-analysis

Abstract: BACKGROUND: Adductor canal block (ACB) has emerged as an effective analgesic regional technique for major knee surgeries in the last decade. Its motor-sparing properties make it particularly attractive for ambulatory knee surgery, but evidence supporting its use in ambulatory arthroscopic knee surgery is conflicting. This systematic review and meta-analysis evaluates the analgesic effects of ACB for ambulatory arthroscopic knee surgeries. METHODS: We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 67 publications
1
47
2
Order By: Relevance
“…The incidence of side effects was similar between the two groups. Opioid-related adverse effects such as postoperative nausea and vomiting, antiemetic use, and postoperative sedation/drowsiness were reported in previous studies [39,40], but we did not find significant differences between the two groups in this study. This could be because the difference between the two groups in PCA consumption was not large enough to cause sufficient differences in side effects.…”
Section: Discussioncontrasting
confidence: 82%
“…The incidence of side effects was similar between the two groups. Opioid-related adverse effects such as postoperative nausea and vomiting, antiemetic use, and postoperative sedation/drowsiness were reported in previous studies [39,40], but we did not find significant differences between the two groups in this study. This could be because the difference between the two groups in PCA consumption was not large enough to cause sufficient differences in side effects.…”
Section: Discussioncontrasting
confidence: 82%
“…In a 2part meta-analysis Vorobeichik and Sehmbi et al found that neither the femoral nerve or adductor canal block significantly reduced opioid requirements compared to multimodal analgesia following ACLR and did not support the routine use of either block for patients having ACLR [14]. Our results from the adductor canal only group support this recommendation for patients undergoing MPFLR.…”
Section: Discussioncontrasting
confidence: 64%
“…Multi‐modal analgesia alone is a common strategy in the management of ambulatory knee surgery due to its ease of adminsitration, long history of use and limited access globally to regional anaesthesia. This strategy, in the absence of any local anaesthetic administration, remains critical given that the difference in pain scores in minor arthroscopic procedures are only modestly worse compared with multi‐modal analgesia in conjunction with regional anaesthesia . Systemic analgesics avoid the potential risks of local anaesthetic toxicity, nerve damage, muscular weakness and local anaesthetic‐induced chondrotoxicity all together .…”
Section: Analgesic Strategiesmentioning
confidence: 99%
“…To date, the reported analgesic benefits of adductor canal blocks in the setting of ACL reconstruction are limited. When compared with either femoral nerve block or placebo in the context of multi‐modal analgesia, the adductor canal block does not reduce pain scores or analgesic consumption, nor does it have any effect on patient satisfaction . A brief assessment of the dermatomal distribution of these nerves alludes to why this might be the case (Fig.…”
Section: Analgesic Strategiesmentioning
confidence: 99%